2012
DOI: 10.3727/096368911x605510
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Conventional, But Not Cloned, Mesenchymal Stem Cells Suppress Lymphocyte Proliferation and Prevent Graft-Versus-Host Disease in Rats

Abstract: Bone marrow-derived mesenchymal stem cells (MSCs) could exert a potent immunosuppressive effect, and therefore may have a therapeutic potential in T-cell-dependent pathologies. In the present study, we aimed to determine whether MSCs could be used to control graft-versus-host disease (GvHD), a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). MSCs were isolated from Lewis rat bone morrow and then cultured in 10% FBS DMEM at 37°C for 4 weeks. The enriched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…MSCs are known to have pleiotropic actions; not only do they exert trophic and anti-inflammatory effects on damaged tissues by producing a variety of trophic factors and cytokines, they also modulate immunologic reactions, which is the basis for their application in graft-versus-host disease [3,4,5]. MSCs that have long been debated to have pluripotency, because they show spontaneous differentiation into mesodermal, ectodermal, or endodermal cells with a very low frequency and are known to home to the damaged site and contribute to tissue repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs are known to have pleiotropic actions; not only do they exert trophic and anti-inflammatory effects on damaged tissues by producing a variety of trophic factors and cytokines, they also modulate immunologic reactions, which is the basis for their application in graft-versus-host disease [3,4,5]. MSCs that have long been debated to have pluripotency, because they show spontaneous differentiation into mesodermal, ectodermal, or endodermal cells with a very low frequency and are known to home to the damaged site and contribute to tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs exert trophic and repair effects and have been applied therapeutically with various kinds of diseases for tissue regeneration and functional restoration [4,5]. The scientific basis for the repair effect of MSCs, however, has not been clearly elucidated.…”
Section: Potential Of Muse Cells In Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Many of these, including CD63, CD81, moesin, Alix, TSG101, and HSP70, are enriched in exosomes. The effect of exosomes in vitro has mostly been focused on their interaction with the immune system, including dendritic cell maturation, and Treg and B cell responses 111, 125, 126 . Exosomes isolated from cardiac progenitor cells in culture protect from ischemia/reperfusion (I/R) injury when injected into the myocardium 103 .…”
Section: Introductionmentioning
confidence: 99%
“…A combination therapy with MSCs and Treg cells, for example, seems to increase the immunomodulatory activity of MSCs (Kitazawa et al, 2012;Lim et al, 2014). Using in vitro and in vivo experiments, Jang et al demonstrated that placenta-derived MSCs transplanted into mice can control GVHD after hematopoietic stem cell transplantation .…”
Section: Adult Stem Cellsmentioning
confidence: 99%